2020
DOI: 10.1002/anie.202010697
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Tertiary Carbon Center in the Formation of Congested C−O Ether Bonds

Abstract: Nucleophilic substitutions, including SN1 and SN2, are classical and reliable reactions, but a serious drawback is their intolerance for both bulky nucleophiles and chiral tertiary alkyl electrophiles for the synthesis of a chiral quaternary carbon center. An SRN1 reaction via a radical species is another conventional method used to carry out substitution reactions of bulky nucleophiles and alkyl halides, but chiral tertiary alkyl electrophiles cannot be used. Therefore, a stereospecific nucleophilic substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…In this case, the main coupling product, 3h , was the only product. Very recently, Kürti’s group and our group reported the alkoxylation of nonchiral α-bromocarboxamides as tertiary alkyl sources in the presence or absence of a Cu catalyst. These results indicated that the main intermediate was not an aziridinone.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the main coupling product, 3h , was the only product. Very recently, Kürti’s group and our group reported the alkoxylation of nonchiral α-bromocarboxamides as tertiary alkyl sources in the presence or absence of a Cu catalyst. These results indicated that the main intermediate was not an aziridinone.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous reports, the nucleophilic substitution of sterically hindered alkyl bromides, especially those with electron-withdrawing groups, is difficult to proceed through either S N 1 or S N 2 pathways. , For example, no product was observed when 2e was treated with 3a under weakly basic conditions that were applied to Cu-catalyzed reactions (eq ). When a stronger base, a polar aprotic solvent, and higher temperature that benefit S N 2 reactions were applied, compounds 12 and 13 were produced instead, presumably through an elimination/Michael addition sequence (eq ).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the congested C−O ether bond is very difficult to construct using Williamson ether synthesis 14 or other S N 2 15 or S N 1 16 reactions. Recent progress in this area has been made by Kurti, 17 Gong, 18 and Nishikata, 19 et al via cross-coupling tertiary alkyl electrophiles with alcohols for the synthesis of a quaternary carbon center. In spite of the above achievements, efficient C−O bond formation between hydroxylamines and tertiary or secondary alkyl halides remains rare, potentially due to the intrinsically low nucleophilicity of OH-hydroxylamine and the rather labile N−O bond.…”
mentioning
confidence: 99%
“…Among them, the congested C–O ether bond is very difficult to construct using Williamson ether synthesis or other S N 2 or S N 1 reactions. Recent progress in this area has been made by Kürti, Gong, and Nishikata, et al. via cross-coupling tertiary alkyl electrophiles with alcohols for the synthesis of a quaternary carbon center.…”
mentioning
confidence: 99%